Imbalance between Goals and Organizational Structure in Primary Health Care in Iran- a Systematic Review. - Mehdi Zanganeh Baygi; Hesam Seyedin (Tehran University of Medical Sciences, 2013)
In recent years, the main focus of health sector reforms in Iran is the family physician and referral system plan. Fundamental changes in the goals and strategies, has increased the necessity of the need to reform the organizational structure. This study tries to review and summarize all cases about the organizational structure of Iran and its challenges in primary health care system.This study was a systematic review of published and grey literature. We searched the relevant databases, bibliography of related papers, and laws, using appropriate search strategies and key words. The CASP tool was used by two experts to evaluate the quality of retrieved papers and inconsistencies were resolved by discussion.After removal of duplicate citations, a total of 52 titles were identified through database searching, among which 30 met the inclusion criteria. Considering the research quality criteria, 14 papers were recognized qualified, which were categorized into two groups of: articles and policies. The results showed ineffectiveness of the current organizational structure at different level. The majority of the papers recommend performing reforms in the system because of changes in goals and strategies. Also, some suggest an appropriate information system to be designed in the current structures. Centralization and delegation process are the main discussions for the studies.Because of fundamental changes in goals and strategies, reforms in the organizational structure of primary health system in Iran especially in peripheral levels are highly recommended.